Comparative analysis of repeat content in plant genomes, large and small - Argentin, Joris; Bolser, Dan; Kersey, Paul J.; Flicek, Paul (Frontiers in Plant Science, 2023)
The DNA Features pipeline is the analysis pipeline at EMBL-EBI that annotates repeat elements, including transposable elements. With Ensembl's goal to stay at the cutting edge of genome annotation, we proved that this pipeline needed an update, and to make this update. We then created a new analysis that allowed the Ensembl database to store repeat classification from the PGSB repeat classification (Recat). This new dataset was then fetched using Perl scripts, and used to prove the gain in sensitivity by the pipeline. Finally, we performed a comparative analysis of transposable element distribution in all plant species available in the Ensembl core database, raising new question about transposable elements in certain branches of the taxonomic tree.